The Reckoning: The Return of Genomic Results to 1444 Participants Across the eMERGE3 Network. Issue 11 (November 2022) - Leppig, Kathleen A.; Rahm, Alanna Kulchak; Appelbaum, Paul; Aufox, Sharon; Bland, Sarah T.; Buchanan, Adam; Christensen, Kurt D.; Chung, Wendy K.; Clayton, Ellen Wright; Crosslin, David; Denny, Josh; DeVange, Shannon; et al.
Abstract : (Abstracted from Genet Med 2022;24:1130–1138) As increased accessibility to genetic testing contributes to finding more individuals with genetic predispositions to a specific conditions or diseases, National Institutes of Health–sponsored networks grow in importance when considering the identification and subsequent management of these conditions. The American College of Genetics and Genomics (ACMG) designated 59 genes (this is now higher with subsequent versions of the guideline) as highly actionable owing to availability of effective medical management guidelines for individuals with detected disease-causing variants in one of these genes.